A Critical Discourse Analysis of Overtourism Narratives in English Travel Journalism - Aprilia Sari Rahayu; Meidiana Eka Putri; Arria Khotimah (LPPM Universitas Dhyana Pura, 2026)
This study critically examines how overtourism is discursively constructed in English-language travel journalism. Grounded in Critical Discourse Analysis (CDA), the research investigates the linguistic and rhetorical strategies used to represent overtourism, tourism actors, and affected communities. Specifically, it analyzes discursive features such as lexical choices, representations of agency, evaluative language, modality, and ideological positioning that shape readers’ perceptions of overtourism. Employing a qualitative descriptive methodology, the study draws on a corpus of travel journalism articles addressing overtourism published in international media outlets. The findings reveal that overtourism is predominantly framed as a global and systemic phenomenon through neutralized agency, passive constructions, and expert-oriented voices. Tourists are discursively positioned in ambiguous roles, portrayed simultaneously as contributors to and victims of overtourism. These strategies produce a balanced yet depersonalized narrative that foregrounds sustainability, responsibility, and policy-oriented solutions. The study contributes theoretically to discourse studies and offers practical implications for tourism communication and English language pedagogy, particularly in the areas of critical reading and media literacy.